PENGARUH CORPORATE GOVERNANCE TERHADAP GREEN BANKING DISCLOSURE (STUDI PADA PERUSAHAAN PERBANKAN DI INDONESIA YANG TERDAFTAR DI BEI PERIODE 2018 – 2020) - San Petro; Rini Octavia; Muhammad Ichsan Diarsyad (Universitas Indo Global Mandiri, 2023)
This research aims to analyze the influence of Corporate Governance on Green Banking Disclosure in bankingcompanies listed on the Indonesia Stock Exchange during the period of 2018 - 2020. Corporate governance plays acrucial role in ensuring transparency and accountability within companies, as well as supporting their efforts inimplementing sustainable and responsible business practices towards the environment. In this study, CorporateGovernance is measured through three variables: Board of Commissioners, Independent Commissioners, andInstitutional Ownership. The Board of Commissioners is considered as one of the institutions responsible for decisionmakingwithin the company. The number of board members is an important indicator in this research, as a larger boardsize allows for diverse perspectives and expertise to be applied in the decision-making process. Additionally,Independent Commissioners are also a significant factor in maintaining the independence and integrity of thecompany's oversight. In this study, the proportion of Independent Commissioners compared to the total number ofcommissioners is used as a measure of their presence and independence. Institutional Ownership is another variable ofinterest in this research. Institutional ownership reflects the participation and involvement of financial institutions andinstitutional investors in the ownership of company shares. The percentage of institutional ownership in relation to thetotal outstanding shares is measured to gain insights into the extent of financial institutions' role in decision-makingand oversight within the company. Green Banking Disclosure is the main focus of this study. Green Bankingencompasses banking practices that prioritize environmental sustainability. Green Banking Disclosure is measuredusing the Green Banking Disclosure Index (GBDI), which covers various aspects such as environmental riskmanagement, sustainable financing, and other environmental initiatives. To test the relationship between thesevariables, the researcher employs multiple linear regression analysis. The data used in this study consists of 96observations, involving 32 banking companies each year. The data is analyzed using the Statistical Package for SocialSciences (SPSS) software to generate generalizable findings.The results of this study indicate that the Board ofCommissioners has a significant positive influence on Green Banking Disclosure in banking companies listed on theIndonesia Stock Exchange during the period of 2018 - 2020. This suggests that a stronger composition and role of theBoard of Commissioners in decision-making lead to higher levels of disclosure of environmentally friendly businesspractices. However, the study did not find a significant relationship between Independent Commissioners and GreenBanking Disclosure, and it found that Institutional Ownership has a significant negative influence on Green BankingDisclosure. These findings provide a deeper understanding of the importance of the role and composition of CorporateGovernance in promoting the disclosure of sustainable business practices in banking companies in Indonesia.Keywords: Board of Commissioners; Independent Commissioners; Institutional Ownership; Green Banking Disclosure